Ice drilling on Princess Elizabeth Land (East Antarctica) aimed to study bedrock and Late Quaternary paleoclimate - G. L. Leitchenkov; P. G. Talalay; N. Zhang; I. A. Abdrachmanov; M. A. Vorobyov; D. Gong; Y. Liu; Y. Li; Y. Sun; I. I. Lavrentiev; A. A. Ekaykin; D. R. Khalimov; et al. (Лëд и снег, 2024)
Targeted bedrock sampling was carried out on Princess Elizabeth Land (30 km south of the coast, at 69.585591° S; 76.385165° E) by drilling through 545 m thick ice. The borehole was drilled using a new, modified version of the cable-suspended Ice and Bedrock Electromechanical Drill (IBED) designed by the Jilin University (China) and under a joint scientific project between VNIIOkeangeologia, Jilin University and China University of Geosciences (Beijing). The drill site is located on the axis of a high-amplitude linear magnetic anomaly that runs parallel to the coast for more than 500 km from Princess Elizabeth Land to Mac. Robertson Land. In the next Antarctic season, borehole geophysical logging will be conducted including temperature measurements for geothermal heat flux calculations.